Robust platform for water harvesting and directional transport. Issue 14 (8th March 2018) - Luo, Hu; Lu, Yao; Yin, Shaohui; Huang, Shuai; Song, Jinlong; Chen, Faze; Chen, Fengjun; Carmalt, Claire J.; Parkin, Ivan P.
Abstract : Water harvesting is used for transforming moisture into available water resources in regions that suffer water scarcity. Abstract : Water harvesting is used for transforming moisture into available water resources in regions that suffer water scarcity. However, it remains a considerable challenge to design a system that functions to both collect water from the air and transport it to a certain region over a long distance. In this work, a new water harvesting platform for dropwise condensation and dropwise transportation is developed to realize both water collection and spontaneously directional transport over long-distance at low temperatures. The water harvesting platform was developed based on a biomimetic slippery liquid-infused porous surface (SLIPS) with micron-size steps and nano-sized holes through electrochemical etching, electrochemical anodizing, low surface energy modification and lubricant infusion. The anti-wetting, chemical resistance, condensation and anti-icing properties of the water harvesting platform at different pHs and temperatures were tested to show the stability of the system. The water harvesting platform exhibited excellent dropwise condensation capacity, and can directly and continuously capture moisture from the air in a low-temperature environment. Spontaneously directional transport of droplets was achieved on a choreographed wedged-platform driven by Laplace pressure, and the transport distance was unlimited due to the energy conversion from surface energy to kinetic energy induced by droplets coalescing in a repeated motion of droplet merging and chasing. This water harvesting platform shows great potential in applications for advanced transportation devices, multifunctional sensors, actuators, and is a promising potential solution to water scarcity.